2013
DOI: 10.1371/journal.pntd.0002310
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs and Practices Related to Dengue Fever: A Focus Group Study

Abstract: BackgroundThis qualitative study aimed to provide an in-depth understanding of the meaning of dengue fever (DF) amongst people living in a dengue endemic region, dengue prevention and treatment-seeking behaviours. The Health Belief Model was used as a framework to explore and understand dengue prevention behaviours.MethodsA total of 14 focus group discussions were conducted with 84 Malaysian citizens of different socio-demographic backgrounds between 16th December, 2011 and 12th May, 2012.ResultsThe study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 21 publications
(18 reference statements)
3
63
0
6
Order By: Relevance
“…Various studies have shown educational messages embedded in a community-based approach, social mobilization and communication can have large impact to reduce Aedes indices compared to fogging activities. [14][15][16][17] Despite this, the LAs have not given sufficient priority to health education activities.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown educational messages embedded in a community-based approach, social mobilization and communication can have large impact to reduce Aedes indices compared to fogging activities. [14][15][16][17] Despite this, the LAs have not given sufficient priority to health education activities.…”
Section: Discussionmentioning
confidence: 99%
“…La disponibilidad limitada de conexión intra-domiciliaria de agua potable también ha sido asociada con la presencia del vector 27,28 . Así mismo, se ha identificado al déficit de información como una barrera en la prevención del dengue, hallazgo similar a lo reportado por otros estudios [29][30][31] , el cual puede provenir de material educativo desactualizado o no contextualizado que conlleva a una baja percepción de la vulnerabilidad hacia la enfermedad por parte de la comunidad 27,28 . El conocimiento insuficiente sobre los criterios actuales de diagnóstico, clasificación y tratamiento del dengue encontrado en los médicos generales, se constituye en una barrera más para la prevención del dengue, similar a lo encontrado en la región Lambayeque, en donde el nivel de conocimiento sobre el dengue fue asociado con la oportunidad de la capacitación.…”
Section: Discussionunclassified
“…Ante estas deficiencias de comunicación en relación al dengue encontrados en los profesionales de salud, es natural comprender que a nivel de la población existan percepciones e información inadecuada sobre el dengue que ameriten ser abordados [32][33][34] . Siendo la participación comunitaria un concepto complejo e integral, el cual abarca a distintos actores, diversos estudios asocian la baja participación comunitaria, a diversos entes gubernamentales responsables de la prevención 29,30,33 . Las limitaciones del personal de salud para involucrar a la comunidad y la falta de motivación y compromiso comunitario son algunas de las causas reportadas sobre la escasa participación comunitaria 33 .…”
Section: Discussionunclassified
See 2 more Smart Citations